Penanganan Sedimentasi dan Penumpukan Sampah di Pesisir Utara Kota Cirebon - Anggi Yus Susilowati; Alfian Febriyanto (UIN Siber Syekh Nurjati Cirebon, 2021)
This study aims to determine the factors that cause sedimentation and garbage accumulation on the coast and to find out how to handle the problem of sedimentation and garbage accumulation on the north coast of Cirebon city. The research method used in this study uses a qualitative approach. Collecting data using observation, interview, and documentation techniques to obtain primary data and secondary data. Data analysis was carried out using an interactive data analysis model and data validation was carried out using technical triangulation techniques. The results showed that the factors causing sedimentation and garbage accumulation on the coast were caused by natural and non-natural factors. And the handling that can be done is by solving practical and strategic activities